2019
DOI: 10.21203/rs.2.15211/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of calcitonin-gene-related peptide binding monoclonal antibodies for the preventive treatment of episodic migraine – An updated systematic review and meta-analysis

Abstract: Background: Migraine is one of the most common neurological disorders that leads to disabilities. However, the conventional drug therapy for migraine is unsatisfactory. Therefore, this meta-analysis aimed to evaluate the efficacy and safety of calcitonin-gene-related peptide binding monoclonal antibody (CGRP mAb) for the preventive treatment of episodic migraine, and provide high-quality clinical evidence for migraine therapy. Methods: A systematic electronic database search was conducted to identify the poten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…In addition to MSMDs, we performed a subgroup analysis of the above outcomes, which showed that CGRP mAbs showed signi cant e cacy in both episode migraines and chronic migraines, and the results were reliable and stable. The results were similar to those of previous meta-analyses, which included only episodic migraines or chronic migraines [14,[35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to MSMDs, we performed a subgroup analysis of the above outcomes, which showed that CGRP mAbs showed signi cant e cacy in both episode migraines and chronic migraines, and the results were reliable and stable. The results were similar to those of previous meta-analyses, which included only episodic migraines or chronic migraines [14,[35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…With this abundance of free circulating CGRP, it should not be surprising that rimegepant acute treatment could provide additional therapeutic benefit. Since the 3 ligand‐targeting CGRP mAbs (fremanezumab, galcanezumab, eptinezumab) exhibit similar treatment effects on migraine prevention, 27 it is likely that all 3 leave comparable free levels of CGRP circulating during mAb treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Calcitonin gene-related peptide (CGRP), a 37-amino-acid neuropeptide, is widely distributed in central and peripheral nervous system (17,18). It is well documented that CGRP is essential for the modulation of orofacial pain, especially migraine (19,20). Our previous study revealed that CGRP played an important role in the modulation of orofacial pain (21).…”
Section: Introductionmentioning
confidence: 98%